Reference values for serum dehydroepiandrosterone-sulphate in healthy children and adolescents with emphasis on the age of adrenarche and pubarche - BEREKET, ABDULLAH; GÜRAN, TÜLAY (WILEY, 2015)
ObjectiveAdrenarche is a component of normal pubertal development. Recent decades have witnessed changes in the timing and tempo of puberty in different populations. We aimed to obtain normative data on dehydroepiandrosterone-sulphate (DHEA-S) secretion in healthy children and to evaluate the age of adrenarche, pubarche and the DHEA-S levels at which pubarche starts in both sexes. MethodsSerum DHEA-S concentrations were measured in 531 healthy (291 female) Turkish children aged 1month-18years by an automated chemiluminescence method. Pubic hair development was evaluated. DHEA-S concentrations >1084nmol/l (40g/dl) were regarded as adrenarche. Age-related normative data were constructed. Age at adrenarche and pubarche and the DHEA-S levels at pubarche were estimated using ROC analyses. ResultsSerum DHEA-S levels were high in the first 6months of life then declined below 1084nmol/l (40g/dl) with a cut-off age of 046years for girls and 061years for boys with 98% and 96% statistical sensitivity. Stable minimum levels were observed for the following 5years. The cut-off age for DHEA-S levels rising above 1084nmol/l (40g/dl) was 80 and 70years for girls for boys, respectively. DHEA-S levels at transition from Tanner stage P1 to P2 was 905nmol/l (334g/dl) in girls and 118nmol/l (436g/dl) in boys. Median (CI) DHEA-S levels were 1707(948-336) and 244(1192-3577) nmo/l [63(35-124) and 90(44-132) g/dl] in girls and boys, respectively, with Tanner stage P2 pubic hair. ConclusionsWe established reference data of serum DHEA-S levels in a large group of children. Currently, adrenarche (DHEA-S>1084nmol/l) starts 1year earlier in boys but higher DHEA-S levels are needed for transition from P1 to P2 in boys.
Keywords: PUBERTY; ANDROGEN; GROWTH; GIRLS; ADRENOCORTICOTROPIN; CHROMATOGRAPHY; MATURATION; CHILDHOOD; STEROIDS; INFANTS